Cross-section-constrained top-quark mass measurement from dilepton events at the tevatron - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
We report the first top-quark mass measurement that uses a cross-section constraint to improve the mass determination. This measurement is made with a dilepton tt̄ event candidate sample collected with the Collider Detector II at Fermilab. From a data sample corresponding to an integrated luminosity of 1.2fb-1, we measure a top-quark mass of 170.7-3.9+4.2(stat)±2.6(syst) ±2.4(theory)GeV/c2. The measurement without the cross-section constraint is 169.7-4.9+5.2(stat)±3.1(syst)GeV/c2. © 2008 The American Physical Society.